Gambaran klinis dan faktor predisposisi dari coated tongue pada mahasiswa gigi klinik Fakultas Kedokteran Gigi Universitas Padjadjaran - Meelaashah Ragunathan; Erna Herawati; Lusi Epsilawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The aim of this research is to find the clinical features and the predisposing factors of coated tongue among clinical dental students in Faculty of Dentistry Universitas Padjadjaran. Material and Methods: The research is a descriptive type where students with coated tongue were observed and specific scores were given based on Miyazaki classification and Gomez classification to measure the distribution and discoloration of the coating on the tongue. For the predisposing factor, a questionnaire was given out to find out the most influential predisposing factor. Results: In this research, 68 clinical dental students were found with coated tongue. Based on Miyazaki classification, 28 have score 1, 29 have score 2 and 11 have score 3. Based on Gomez classification 63 have score 1 (92.6%), 3 have score 2 (4.4%) and 2 have score 3 (3%). coated tongue occur due to soft diet on 29 students (42.6%), medication intake on four students (5.9%), less water intake on 26 students (38.2%) and less fiber intake on nine students (13.2%). Conclusion: Among all clinical dental students in Faculty of Dentistry Universitas Padjadjaran, most of the sample have scored 2 for Miyazaki classification and score 1 for Gomez classification. For the predisposing factors, coated tongue highly occured due to soft diet followed by less water intake, less fiber intake and medication intake.